(untitled) (Interfaces: A Journal of Medieval European Literatures, 2020)
This article examines the use of reported discourse in Villehardouin’s La Conquête de Constantinople (c. 1210), offering a comparison to Robert de Clari’s text of the same name. The radical shift in direct speech across the first and second halves of the text is explored in relation to three existing interpretations put forward by scholars, before a fourth one is proposed that places new emphasis on the processes of memory and text-making behind the composition of the Conquête. Villehardouin’s status as eyewitness, and the importance this has for the nature of his chronicle, is then analysed through a reading of the 2009 novel Jan Karski by Yannick Haenel, whose playful, distortional treatment of historical speech and metacommentary on the act of bearing witness have important implications for the temporality and discursive features of the medieval text.